Dearomatization‐Rearomatization Strategy for ortho‐Selective Alkylation of Phenols with Primary Alcohols - Yu, Jianjin; Li, Chao‐Jun; Zeng, Huiying (Angewandte Chemie International Edition, 2021)
Phenols are common precursors and core structures of a variety of industrial chemicals ranging from pharmaceuticals to polymers. However, the synthesis of site‐specifically substituted phenols is challenging, and thus the development of new methods for this purpose would be highly desirable. Reported here is a protocol for palladium‐catalyzed ortho‐selective alkylation reactions of phenols with primary alcohols by a dearomatization‐rearomatization strategy, with water as the sole by‐product. Various substituted phenols and primary alcohols were compatible with the standard reaction conditions. The detailed mechanism of this transformation was also investigated. A dearomatization‐rearomatization strategy was developed for palladium‐catalyzed cross‐coupling reactions of phenols and inexpensive primary alcohols to site‐specifically generate ortho‐alkyl‐substituted phenols. Water was the sole by‐product of the reaction, making it a green method for site‐specific synthesis of these phenols.